Analyzing poverty levels and welfare: Does cigarette consumption and spending on regional functions have an impact? - Haer, Jamhul; Sarjiyanto, Sarjiyanto (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
In numerous developing nations, the impact of cigarette consumption on poverty often goes unnoticed by policymakers. This study endeavours to explore the correlation between household expenditure on cigarettes and levels of poverty and welfare. Beyond household spending, it also investigates the influence of regional functional expenditures and the prevalence of open unemployment on poverty and welfare. The examination encompasses 100 regencies and cities across three provinces: East Java (38 regencies and cities), West Java (27 regencies and cities), and Central Java (35 regencies and cities). Utilizing secondary data from the Central Statistics Agency (BPS) and the Ministry of Finance of the Republic of Indonesia, collected in 2021, employing a cross-sectional approach, this study employs multiple linear regression analysis via the Stata 17 program to discern the impact of various factors, including household spending, regional functional spending, and control variables, on poverty and welfare. The findings reveal that household cigarette consumption significantly exacerbates poverty, indicating that an increase in such consumption escalates poverty rates. Conversely, the second estimation model demonstrates that increased household expenditure on cigarettes significantly diminishes welfare levels, underscoring the adverse impact of heightened smoking consumption on overall welfare.